The aftermath of enforcement episodes for the children of immigrants. Issue 1 (14th March 2023) - Dreby, Joanna; Macias, Eric
Abstract: For 30 years, U.S. immigration policy has increasingly focused on enforcement. This article goes beyond cataloging the harms of such policies to document the processes by which they become more or less salient in the lives of children of immigrants over time. In‐depth interviews with 86 young adults raised in New York show that enforcement policies shape children's lives either through lived experiences of enforcement episodes or through diffuse fears arising from indirect threats. Qualitative analysis of narratives of (a) deportations post‐incarceration, (b) removals, (c) arrests and detentions (d) direct threats, and (e) diffuse fears identifies characteristics related to each that may affect children even after they age into adulthood.